Geomorphological analysis for assessment of coastal recreation sites in the coastal area of Trisik, Kulon Progo Regency, Yogyakarta Province - Suratman Woro; Tukidal Yunianto (Faculty of Geography, Universitas Gadjah Mada, 1988)
The sand dunes and beach ridges area along the south coast of Yogyakarta Special Region are partly potential for a recreation site. The development of the Trisik Coast in Kulon Progo as a recreational area, is feasible for its natural landscape condition and its location, close to the outlet of Progo River. For this purpose, a basic survey shoal be carried out, in which case, a geomorphological survey may be a part of the survey that contributes to the study of landforms and their processes. Relevant geomorphological aspects, such as morphodynamics of the tidal zone, wind-erosion and flood hazard in the assessment of physical potential of the Trisik coast for recreation have been analysed. Aerial-and ortho-photo interpretation proved to be a useful tool in delineating landforms.